Partial biochemical response of adrenal artery embolization for pheochromocytoma: A case report and review of the literature - Fernando Choque-Chávez, MD; Alfredo Páez-Carpio, MD, MSc, EDIR, EBIR; Mireia Mora, MD, PhD; Silvia Montserrat, MD; Alejandro Pascagaza, MD, EBIR; Marta Burrel, MD, PhD (Radiology Case Reports)
We present the case of a 22-year-old male with a left adrenal pheochromocytoma, initially diagnosed during a workup for thoracic pain. The patient's tumor was refractory to medical management, and surgical resection was ruled out due to high cardiovascular risk, stemming from cyanotic congenital heart disease, aortic aneurysm, and factor VII deficiency. The patient underwent adrenal artery embolization (AAE) as a salvage treatment. Following the procedure, there was an initial reduction in hypertensive crises and biochemical markers, with plasma normetanephrine levels decreasing from 1490 pg/mL to 313 pg/mL. However, over subsequent months, the patient experienced symptom recurrence, and biochemical relapse occurred, with normetanephrine levels rising to 742 pg/mL by 3 months postprocedure. This case highlights the potential for AAE to provide short-term symptom relief and biochemical response; nevertheless, it may not be an effective long-term curative option. More collaborative and prospective studies are needed to assess its success and efficacy.